ANALISIS EFISIENSI PENGELOLAAN DANA ZAKAT PADA BAITUL MAL PROVINSI ACEH - Afrida, Eka; Amin, Ali (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The purpose of this research is to know and to analyze the management efficiency of zakat fund at Baitul Mal, Aceh Province. This research is descriptive Qualitative. The data used in this research is primary data by interviewing the important people at the institution and financial data provided by the Baitul Mal Aceh (BMA). The result of this research is the management of zakat fund which is conducted by Baitul Mal Aceh in 2012 to 2015 has not been efficient. This is because of the amount of salary both civil servants and non-civil servants increase every year that cause the zakat income was increase, whereas the distribution of zakat has not been optimal. As a result, the zakat acceptance in Aceh is not evenly distributed, there were still many people who were entitled to receive zakat has not received its part due to the management of zakat funds conducted by baitul mal was not efficient yet. The average of inefficiency rate of zakat fund management in 2012 to 2015 period at Baitul Mal Aceh is 60,75%.